Metodologia didática para o desenvolvimento de uma docência transdisciplinar - Alves, Lucicleide Araújo de Sousa (2010)
The issue in this academic research attempted to investigate the occurrence of didactic processes in the construction of knowledge in presence teaching and learning environments from Complexity and Transdisciplinarity.